Cultural regeneration through urban design in Algeria. The case of Leonardo Fibonacci’s promenade in Bejaia - Mouhoubi Nedjima; Bakour Amira Kahina (E3S Web of Conferences)
Sustainable urban development requires the use of all available means, given the increasing competitive status of cities. Cultural regeneration is a widely used tool for urban development. This culture, which can be expressed in a multitude of ways, frequently necessitates physical places for its practice, in spite of the virtual advantages. The public realm represents the optimal places for the expression of culture. The urban design in charge of these spaces should, therefore, focus on the impact it may have on the cultural regeneration of the entire city through the design of its public urban spaces, which should highlight and develop the originality of places and cultures. Indeed, “public realm” is the fundamental element of urban design, which aims to create social links and interactions in order to promote urbanity and union. In previous decades, this was problematic due to the challenges of industrialization, urbanization and large residential complexes. Thus, culture represents the pillar of these spaces in order to create cohesion and social interaction. The case of Leonardo Fibonacci’s promenade in Bejaia, Algeria, demonstrates the effectiveness of attractive public realm design as a means of cultural regeneration. The latter extends to cultural interaction and diversification to enhance inclusiveness.